2005
DOI: 10.1016/j.jhazmat.2005.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Leaching behaviour of a galvanic sludge in sulphuric acid and ammoniacal media

Abstract: Leaching studies of a sludge produced by the physico-chemical treatment of wastewaters generated by a Ni/Cr plating plant were carried out in both sulphuric acid and ammoniacal media aiming to decide which of them would be the best treatment for this kind of waste material. The dissolution behaviour of some metals (Cu, Ni, Cr and Zn) was studied in order to assure the best metal recovery conditions in subsequent processes by the use of some separation methods such as solvent extraction and precipitation techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 15 publications
4
32
0
2
Order By: Relevance
“…The optimum conditions are: L/S of 3:1, pH of 10.8~11.2, ammonia concentration of 20%, extraction time of 1.5 h, stirring speed of 2000 rpm, and four stages of extraction. Impurities such as Mg, Zn, and Al hardly leached, and reported to leaching residue [26]. These experimental results lay a good foundation for future studies into the recovery of copper and nickel.…”
Section: Effect Of Leaching Parameters On the Extent Of Leaching Of Cmentioning
confidence: 57%
“…The optimum conditions are: L/S of 3:1, pH of 10.8~11.2, ammonia concentration of 20%, extraction time of 1.5 h, stirring speed of 2000 rpm, and four stages of extraction. Impurities such as Mg, Zn, and Al hardly leached, and reported to leaching residue [26]. These experimental results lay a good foundation for future studies into the recovery of copper and nickel.…”
Section: Effect Of Leaching Parameters On the Extent Of Leaching Of Cmentioning
confidence: 57%
“…This author concluded that alkaline leaching is much more selective, but the overall efficiency in valuable metals extraction is low. Silva et al [12] published a comparison between acid and alkaline media in galvanic sludge leaching and the conclusions were similar.…”
Section: Introductionmentioning
confidence: 78%
“…All the leach samples (referenced therein as samples A-E) were generated from sulphuric acid leaching of a polymetallic complex sludge using a 100 g/L sulphuric acid solution and a liquid to solid ratio (L/S) of 5:1 [24]. The sludge was produced by the physicochemical treatment of wastewaters from a Ni/Cr plating plant located at Braga, in the north of Portugal.…”
Section: Generation Of Leach Samplesmentioning
confidence: 99%